Budget Transparency and Legislative Budgetary Oversight: An International Approach. (September 2016) - Ríos, Ana-María; Bastida, Francisco; Benito, Bernardino
This article attempts to evaluate the role the legislative budgetary oversight plays in enhancing budget transparency. This relationship has not been empirically tested so far. For a sample of 93 countries surveyed by International Budget Partnership in 2010, we show that, as expected, legislative budgetary oversight has a positive influence on budget transparency. Besides, the legal system, political competition, and economic level are also found to affect budget transparency. As an additional analysis, we investigate the determinants of legislative budgetary oversight along the budgetary process. In this vein, the type of legislature, legal system, Supreme Audit Institution's budgetary oversight, economic level, and democratic level determine legislative budgetary oversight.